1958
DOI: 10.2118/912-g
|View full text |Cite
|
Sign up to set email alerts
|

Miscible Displacements of Reservoir Oil Using Flue Gas

Abstract: Published in Petroleum Transactions, AIME, Volume 213, 1958, pages 7–10. Summary Miscible phase displacement of oil from reservoirs has been emphasized in the past few years. The reason for this emphasis lies in the high oil recovery attainable by this process. Removal of capillary effects in the reservoir leads to recoveries approaching 100 per cent in the area contacted by the miscible phase. The miscible slug process is one means of obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1967
1967
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Injecting flue gas into oil reservoirs to enhance oil recovery has been studied for nearly 60 years . Coinjection of steam and flue gas directly from the steam generator to carry out CSS and SAGD has been proven successful by pilot tests. ,, This technology has the potential to reduce steam heat loss, promote the development of the steam chamber, reduce the cost of injection substantially, provide a means to sequester some of the exhaust gas from steam generation, and capture CO 2 in the oil reservoir …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Injecting flue gas into oil reservoirs to enhance oil recovery has been studied for nearly 60 years . Coinjection of steam and flue gas directly from the steam generator to carry out CSS and SAGD has been proven successful by pilot tests. ,, This technology has the potential to reduce steam heat loss, promote the development of the steam chamber, reduce the cost of injection substantially, provide a means to sequester some of the exhaust gas from steam generation, and capture CO 2 in the oil reservoir …”
Section: Resultsmentioning
confidence: 99%
“…Laboratory research 8 , 14 16 and field applications 17 , 18 have shown that CO 2 and N 2 are two beneficial components for heavy oil EOR. A series of pressure–volume–temperature (PVT) experiments were conducted to study the solubility of CO 2 , N 2 , and their mixtures in heavy oil and their effect on swelling, density, and viscosity reduction of heavy oil.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…− The MMP is determined in a set of experiments at different displacement pressures at 1.2 V pore injected into the slim model. The MMP corresponds to the breakpoint of the displacement factor -displacement pressure curve [30,41,42], as well as a number of others [42][43][44].…”
Section: Research Proceduresmentioning
confidence: 99%
“…88% N2, 12% CO2) or carbon dioxide for displacement of oil from reservoirs, tests were made by contacting or repressuring samples of oil with these gases. Measurements were made on "swelling" of the oil volume and decrease of oil viscosity due to solution of the gas in the oil (36,56).…”
Section: Reservoir Fluids and Their Usesmentioning
confidence: 99%